EVALUASI PROGRAM PELALAWAN TERANG DI KABUPATEN PELALAWAN - Yudi Ari Pratama; Hasim As'ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Pelalawan Bright Program is one of the strategic programs of the Pelalawan Regency government which is contained in the Pelalawan Regency Regional Regulation. This program is an effort to increase household electrification and the use of electricity resources to support economic, social and cultural activities by facilitating the construction of power plants and the construction of electricity networks to remote areas. However, in the implementation of the Pelalawan Terang program, there are still some problems. Where there are areas that do not have electricity and there are areas that have not enjoyed full electricity 1 X 24 hours. Based on the phenomena that occurred, the researchers were interested in conducting research related to the Evaluation of the Bright Pelalawan Program in Pelalawan Regency. The purpose of this study is to find out how the Context, Input, Process, and Product of the Pelalawan Terang program in Pelalawan Regency and identify the factors that hinder the implementation of the program. The theory used is the program evaluation theory by Stufflebeam, namely there are four evaluation components: Context, Input, Process, and Product. The type of research used is descriptive qualitative research and the data source comes from primary data and secondary data obtained through interview, documentation, and observation techniques for further analysis using interactive model data analysis techniques. The results of this study indicate that the context of the Pelalawan Terang program in Pelalawan Regency is good. The input from the Pelalawan Bright program in Pelalawan Regency is not good. The process of the Pelalawan Terang program in Pelalawan Regency is not good. The product of the Pelalawan Terang program in Pelalawan Regency is already good. The factors that hinder the implementation of the Pelalawan Terang program in Pelalawan Regency are: Program Funding, Program Supervision, and Program Realization.   Keywords: Light Pelalawan, Program Evaluation, Evaluation